In vitro Screening of Bryophytes for Antimicrobial Activity - R G Bodade; P S Borkar; Md Saiful Arfeen; C N Khobragade (Institue of Medicinal Plants, ACECR, 2008)
Background: Bryophytes, the previous land plants posses medicinally important bioactive compounds but with little information. Traditionally the bryophytes plants posses some bioactive components and therefore used throughout the world as drugs and remedies to cure the various diseases.   Objectives: Evaluation of antimicrobial effect of mentioned bryophytes on some pathogenic microorganisms.   Methods: Different Solvent fractions of selected bryophytes were obtained and dried in vacuum. Antimicrobial effect of these fractions was determined by agar diffusion method on different pathogenic microorganisms. The result was then compared with the standard antibiotics ampicillin and nystatin (10 ug/ml).   Results: Results indicated that the bryophyte extracts were found to be active against at least one of the test organisms except Racomitrium crispulum. The extracts that displayed antibacterial activity were neither always effective against the same organisms, nor consistent in magnitude of inhibition. Ethanolic, acetone and chloroform extracts were found to be more effective on Escherichia coli and Staphylococcus aureus. Among the fungi Aspergillus niger was most sensitive to the ethanolic extract of Plagiochasma appendiculatum and Bryum argentium. Conclusion: Ethanolic, acetone and chloroform extract of nearly all bryophytes were found to be effective, therefore the study focuses on medicinal significance of bryophytes .